EVALUASI KESESUAIAN PERKULIAHAN MICROTEACHING PENDIDIKAN FISIKA TERHADAP KKNI DI UIN SUNAN KALIJAGA YOGYAKARTA - Fuady, Arina Izataki; Prasetyo, Zuhdan Kun (Jurnal Inovasi Pendidikan IPA, 2015)
Evaluation of suitability evaluation of physics education microteachig class to KKNI in Sunan Kalijaga Islamic University was done by stake model with quantitave descriptive analysis. Based on data analysis indicate that (1) the suitability of planning class to the achievement of KKNI Level 6 phisics education at 45.45% ( enough categorized); (2) the suitability of the implementation of class held on the achievement KKNI Level 6 physics education viewed through the achievement of the student's ability to KKNI Level 6 at 75.34% (very well categorized) and the role of the lecturer to the achievement of the students ability to KKNI Level 6 amounting to 55.01% (enough categorized); and (3) the conformity assessment of the achievement of the lecturers do KKNI Level 6 physical education by 72.73% (well categorized).